Ekonomiczno- finansowa problematyka rozwoju roli rad narodowych w ochronie zdrowia w Polsce Ludowej - Sobiech, Jan (Wydział Prawa i Administracji UAM, 1976)
The author of the paper deals with the changes in the financial sources and organization of health service in Poland after World War II. The special emphasis is put on the role of regional branches of health care. The actuale position of these branches is based on central planning. Therefore, this article deals with the changes in the planning system and budgeting. On the article the author presented most important conceptions connected with the problem and drew conclusions from discusions concerning the changes in planning.
The Role of People's State Councils in the Health Care in the Polish People's Republic and Its Economic and Financial Implications